(untitled) (Journal of Education and Development, 2023)
Business schools need to maintain student academic satisfaction. A key component of a business school’s curriculum is its core or required courses and online courses experiences. Using qualitative open item analyses, this study asked graduating business students for their perceptions of required core courses and their online course experiences. Consistent demographics and school background variables allowed the Fall, 2021 and Spring 2022 graduating samples to be combined. Student records allowed the graduating students to be split into qualitative versus quantitative majors to promote comparison across common categories. There was much overall agreement between qualitative and quantitative majors on the most valuable part of their core experience, as well as how to improve this experience. However, quantitative majors were more likely to mention specific core courses as being valuable than qualitative majors. In addition, quantitative majors were more likely to voice concerns about better professor instruction and poor course structure versus qualitative majors. Finally, quantitative majors were more likely to express that online courses were not as learning effective as in-person courses. Results are further discussed.